Study on Process of CoNiCrAlY Bonding Layer Under Laser Shock. Issue 3 (1st April 2020) - Hua, Yinqun; Zhu, Jiaming; Chen, Ruifang; Shuai, Wenwen
Abstract : In this paper, atmospheric plasma spraying (APS) was used for the preparation of a CoNiCrAlY bonding layer on nickel-based superalloy with different laser shock times designed for surface modification; in addition, electron beam physical vapor deposition (EB-PVD) was used to deposit a ceramic layer to form a new modified coating. When comparing high-temperature oxidation resistance with mechanical properties for both traditional coatings and modified coatings as well as the effects of different laser shock times on them, the results showed that the cross-section hardness of the coating under two laser shocks reaches the peak value of 297 HV which is 11% higher than that of ordinary coating; the growth rate of the thermal growth oxide at the interface of the modified coatings are significantly lower than that of the ordinary coating under different oxidation times at 1000°C, furthermore, the lowest rate, 2.43E-4 μm/h occurs after laser shock twice; with the increase of oxidation time, the residual compressive stress generated during the oxidation increases first and then decreases, moreover, the stress value of the modified coating after laser shock twice is the smallest. To conclude, this research is of significance for application in surface modification for aviation.